JKN Claim Optimization Strategy in Indonesian Hospitals: Literature Review - Simon Jonatan (CV. AFDIFAL MAJU BERKAH, 2026)
National Health Insurance (JKN) claims management in Indonesian hospitals still faces various obstacles, such as high pending claims, incomplete medical records, diagnostic and treatment coding errors, limited human resource (HR) competency, and suboptimal integration of the Hospital Management Information System (SIMRS) with the BPJS Kesehatan application. These conditions result in delays in claim disbursement, cash flow disruptions, and the risk of declining service quality. This literature review aims to identify the main factors causing delayed claims and summarize effective JKN claim optimization strategies in Indonesian hospitals. Methods: A literature search was conducted on Google Scholar, Garuda, and DOAJ databases for articles published in 2022–2025 with keywords related to JKN/BPJS claims, INA-CBGs, pending claims, claims management, and SIMRS. Articles that met the inclusion criteria were analyzed narratively and synthesized based on a management framework (HR, procedures, information technology, and finance). Strategies consistently recommended in the literature include strengthening the competency of coders and internal verifiers through ongoing training, standardizing claims SOPs and strengthening quality control and cost control, optimizing SIMRS–BPJS integration (end-to-end bridging) to ensure the completeness and accuracy of claim files, and strengthening coordination across units and with BPJS Kesehatan.Strategic management approaches (e.g., 4M/5M, POAC, TQM) have been shown to contribute to a reduction in pending claims and accelerated claim disbursement. Optimizing JKN claims requires integrated interventions across human resources, procedures, information technology, and financial governance. Hospitals are advised to adopt a structured strategic management model, establish claims management performance indicators, and accelerate information system integration to improve the timeliness and quality of claims.